Anisotropic phase coherence in GaAs/InAs core/shell nanowires. (6th October 2017) - Haas, Fabian; Zellekens, Patrick; Wenz, Tobias; Demarina, Nataliya; Rieger, Torsten; Lepsa, Mihail I; Grützmacher, Detlev; Lüth, Hans; Schäpers, Thomas
Abstract: Low-temperature transport in nanowires is accompanied by phase-coherent effects, which are observed as modulation of the conductance in an external magnetic field. In the GaAs/InAs core/shell nanowires investigated here, these are h / e flux periodic oscillations in a magnetic field aligned parallel to the nanowire axis and aperiodic universal conductance fluctuations in a field aligned perpendicularly to the nanowire axis. Both electron interference effects are used to analyse the phase coherence of the system. Temperature-dependent measurements are carried out, in order to derive the phase coherence lengths in the cross-sectional plane as well as along the nanowire sidewalls. It is found that these values show a strong anisotropy, which can be explained by the crystal structure of the GaAs/InAs core/shell nanowire. For nanowires with a radius as low as 45 nm, flux periodic oscillations were observed up to a temperature of 55 K.